The impact of surface and geometry on coefficient of friction of artificial hip joints. (August 2017) - Choudhury, Dipankar; Vrbka, Martin; Mamat, Azuddin Bin; Stavness, Ian; Roy, Chanchal K.; Mootanah, Rajshree; Krupka, Ivan
Abstract: Coefficient of friction (COF) tests were conducted on 28-mm and 36-mm-diameter hip joint prostheses for four different material combinations, with or without the presence of Ultra High Molecular Weight Polyethylene (UHMWPE) particles using a novel pendulum hip simulator. The effects of three micro dimpled arrays on femoral head against a polyethylene and a metallic cup were also investigated. Clearance played a vital role in the COF of ceramic on polyethylene and ceramic on ceramic artificial hip joints. Micro dimpled metallic femoral heads yielded higher COF against a polyethylene cup; however, with metal on metal prostheses the dimpled arrays significantly reduced the COF. In situ images revealed evidence that the dimple arrays enhanced film formation, which was the main mechanism that contributed to reduced friction.